2021
DOI: 10.21203/rs.3.rs-665843/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computer Navigated Total Hip Arthroplasty Via The Direct Superior Approach: A Retrospective Study of The First 30 Consecutive Cases

Abstract: Background The direct superior approach (DSA), which is one of the muscle-sparing approaches for total hip arthroplasty (THA), has been recently reported with positive outcomes. However, in minimally invasive THA, it has been reported that the visual intraoperative estimation of the cup position is not reliable. Therefore, those minimally invasive approaches are associated with the increased risk of acetabular cup malposition due to the limited exposure. Although the positive effects of computer navigation sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Most studies use the Lewinnek safe zone (5-25° anteversion, 30-50° inclination) to measure optimal implant positioning 31 . Five studies reported a mean cup inclination and mean cup anteversion within the Lewinnek safe zone 10,20-22,27 . The DSA showed cup inclination and anteversion comparable with the MPA and PLA 10,27 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies use the Lewinnek safe zone (5-25° anteversion, 30-50° inclination) to measure optimal implant positioning 31 . Five studies reported a mean cup inclination and mean cup anteversion within the Lewinnek safe zone 10,20-22,27 . The DSA showed cup inclination and anteversion comparable with the MPA and PLA 10,27 .…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, no difference in dislocations or infection was reported. Four other observational studies did not find any difference in complication rates between the DSA and the PLA or mini posterior approach (MPA) [11][12][13]27 . Overall, while a RCT with a small sample size suggest a disadvantage for the DSA, larger realworld evidence studies present different outcomes.…”
Section: Complicationsmentioning
confidence: 92%
See 3 more Smart Citations